Using the Deterministic EOQ Formula in Stochastic Inventory Control - Axsäter, Sven (Management Science, 1996)
This note gives an improved bound (√5 − 2)/2 ≈ 0.1180 for the relative cost increase when using the deterministic EOQ formula as a heuristic solution when demands are stochastic. We also discuss under what circumstances this bound is tight.